Sobre algunos conceptos para comprender las relaciones entre religión y guerrilla en la Argentina de los ´60 y ´70 - Luis Miguel Donatello (Nuevo mundo - Mundos Nuevos, 2008)
This article intends to establish a conceptual debate around the terms used to understand the relationships between catholicism and warfare in the Argentina of the' 60 and ' 70. Thus we manage to reconstruct a bibliographic framework on the phenomenon and proposes theoretical alternatives, which may help us to understand the phenomenon of secularization in western societies of the 20th century.